CFD modeling of heat transfer and fluid flow inside a pent-roof type combustion chamber using dynamic model - Varol, Yasin; Öztop, Hakan Fehmi; Firat, Mujdat; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2010)
A numerical work has been performed to analyze the heat transfer and fluid flow in a pent-roof type combustion chamber. Dynamic mesh model was used to simulation piston intake stroke. Revolution of piston (1000 <= n <= 5000) is the main governing parameter on heat and fluid flow. k-epsilon turbulence model was used to predict the flow in the cylinder of a non-compressing fluid. They were solved with finite volume method and FLUENT 12.0 commercial code. Velocity profiles, temperature distribution, pressure distribution and velocity vectors are presented. It is found that the inclined surface of pent-roof type of combustion chamber reduces the swirl effect and it can be a control parameter for heat and fluid flow. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Internal combustion engine; CFD; Heat transfer; Combustion chamber